Understanding Access to Safe Abortion for Women and Girls in Kenya (Discourse of Law and Administration, 2026)
Access to safe abortion in Kenya is impeded by the presence of contradictory laws governing abortion, which has resulted in varied interpretations on the legality of abortion among key stakeholders. The objective of this paper is to discuss the abortion legal landscape in Kenya, the existing legal narratives about abortion and the factors affecting access to safe abortion in Kenya.
Keywords: abortion; reproductive health care; Constitution of Kenya